Penyusunan Rencana Strategis Perusahaan: Innovatech Solutions - Muhammad Sabil Ahror; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
This mini proposal presents the strategic planning design for a hypothetical company, Innovatech Solutions, which operates in software development, AI-based technologies, and digital solutions. In facing the digital era and the Fourth Industrial Revolution, the company must adopt adaptive and sustainable strategies. This proposal includes the formulation of vision, mission, long-term objectives, differentiation strategy, market expansion, human resource development, and digital marketing. Performance evaluation is conducted using the Balanced Scorecard approach and supported by strategic management theories such as SWOT Analysis, Porter’s Generic Strategies, and the Resource-Based View. Through this strategic plan, Innovatech Solutions aims to become a market leader in Southeast Asia.